The transformative role of research in democratic civic education during times of armed conflict - Cohen, Aviv (JSSE - Journal of Social Science Education, 2024)
Highlights: Research highlights how academic inquiry understands and addresses wartime challenges Based on student testimonies, conflict hinders civic engagement and democratic education Educational research can serve as a transformative tool Educational public scholarship and international collaboration are a necessity during crises Purpose: This research explores the pivotal role of educational research in supporting democratic civic education amid armed conflict. The study uses the recent experiences in Israel to examine how research can maintain democratic values and foster reconciliation during tumultuous times, aiming to illuminate the transformative capabilities of academic inquiry in crisis contexts. Approach: The research adopts a semi-empirical, exploratory design that evolved from ongoing events. Personal testimonies from a diverse group of seven students were analyzed for overarching theoretical themes. Findings: The analysis reveals that educational research during conflict may act as a critical, transformative tool, highlighting substantial challenges in maintaining civic engagement and democratic education. It underscores the dual role of research in understanding and actively addressing the complexities of armed conflict. Practical implications: The findings stress the need for educational public scholarship and international collaboration to support democratic education, highlighting the crucial role of researchers in shaping educational practices during crises.